Preparation method of silicon carbide reinforced aluminum-based composite material
Through the two-step sintering method, the oxide film is broken and the liquid phase wettability is improved under vacuum environment, which solves the problem of low sintering density of silicon carbide-enhanced aluminum-based composite materials in the powder metallurgy process, and significantly improves the performance of the material.
Patent Information
- Application Number
- CN202411827176.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing powder metallurgy process prepares silicon carbide-reinforced aluminum-based composites with low sintering density, resulting in poor performance.
The two-step sintering method is adopted. The first step is to sinter under a nitrogen atmosphere to break the oxide film and promote the sintering of aluminum powder particles; the second step is to sintering under a vacuum environment to improve the wettability of the liquid phase, increase the capillary force during the sintering process, and increase the sintering density of the composite material.
The sintering density and performance of silicon carbide-enhanced aluminum-based composite materials were effectively improved by the powder metallurgy process, and materials with a relative density of more than 98.5%.
Smart Images

Figure CN119753438A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum-based composite material preparation, and particularly relates to a method for preparing a silicon carbide reinforced aluminum-based composite material. Background Art
[0002] Silicon carbide particle reinforced aluminum matrix composites have high specific strength and specific modulus and low thermal expansion coefficient. They not only meet the high performance requirements of high-end fields such as aerospace, energy, high-precision machine tools, cutting-edge weapons and automobiles, but also the isotropy of the materials allows the materials to be processed using traditional metal processing technology. All these advantages give it broad application prospects in high-precision fields and civil facilities. However, at present, silicon carbide reinforced aluminum matrix composites are mainly prepared by liquid metal stirring casting, liquid metal impregnation and powder metallurgy, but they all have the limitations of uneven tissue distribution, lengthy processes, low product density or simple shapes.
[0003] Compared with liquid manufacturing technology (stir casting, metal impregnation), powder metallurgy has uniform organization (silicon carbide particles are evenly dispersed in the aluminum matrix) and high production efficiency. The powder is first mixed evenly and then cold pressed into shape, and then the composite is completed through the sintering process. Its characteristics are relatively low requirements for production equipment and can be used for mass production, but the disadvantages are also quite obvious. Products made by powder metallurgy process have low density, high porosity and relatively poor performance. Therefore, for parts with certain mechanical performance requirements, it is necessary to use secondary processing (extrusion, rolling, forging, etc.) for densification.
[0004] At present, the sintering density of silicon carbide reinforced aluminum-based composites prepared by powder metallurgy process is relatively low mainly due to two reasons: 1) There is a dense aluminum oxide film on the surface of the aluminum oxide matrix powder particles, which will hinder the metallurgical bonding of the aluminum alloy powder during the sintering process, making sintering difficult; 2) The aluminum alloy matrix cannot melt during the sintering process, and adding a small amount of sintering aids (such as low-melting-point tin) makes it difficult to achieve complete wetting and filling between particles. In response to the above two problems, existing processes include hot pressing or hot isostatic pressing, which breaks the oxide film in problem 1) by applying pressure during the sintering process to increase the sintering densification of the particles; at the same time, many studies will introduce additive elements for oxide film breaking, such as magnesium, so that it reacts with aluminum oxide and is consumed, while promoting sintering; there is also work that introduces nitrogen during the sintering process to cause the surface oxide film to undergo nitridation reaction, thereby promoting the sintering of aluminum powder particles. Among the above solutions, hot pressing or hot isostatic pressing can promote sintering and improve sintering density, but it has high energy consumption, and the pressed green body structure is relatively simple (cylindrical ingots, blocks, etc.), which makes it difficult to give full play to the technical advantages of powder metallurgy near-net forming. Nitrogen sintering can increase the sintering process to a certain extent, but the subsequent densification driving force is limited, and its sintering density is relatively poor compared with traditional casting and hot pressing. Summary of the invention
[0005] In view of the problem that the silicon carbide particle reinforced aluminum-based composite materials prepared by atmosphere sintering using powder metallurgy technology in the prior art have low density and poor performance, the purpose of the present invention is to provide a method for preparing silicon carbide reinforced aluminum-based composite materials. The present invention adopts a two-step sintering method, which avoids the high energy consumption and simple product structure problems caused by hot pressing and hot isostatic pressing, and at the same time can meet the sintering preparation of complex structure composite materials with high density and high uniformity of organization, effectively improving the technical competitiveness of powder metallurgy technology for preparing silicon carbide reinforced aluminum-based composite materials, and is expected to bring new breakthroughs for the preparation of silicon carbide reinforced aluminum-based composite materials by a new generation of powder metallurgy technology.
[0006] In order to achieve the above object, the present invention adopts the following technical solution: The invention discloses a method for preparing a silicon carbide reinforced aluminum-based composite material. The method comprises the following steps: mixing raw material powder, a binder and an organic solvent to obtain a mixed powder, wherein the raw material powder consists of silicon carbide powder, sintering aid powder and aluminum alloy powder; granulating and sieving the mixed powder in sequence to obtain a composite powder; molding the composite powder to obtain a composite material blank; degreasing the composite material blank to obtain a degreasing blank; sintering the degreasing blank in two steps, wherein the first step is sintered in a nitrogen atmosphere at a temperature of 520-550° C. and a sintering time of 30-60 min; and the second step is sintered in a vacuum environment at a temperature of 600-640° C. and a sintering time of 60-90 min. After the two steps are sintered, the silicon carbide reinforced aluminum-based composite material is obtained.
[0007] The preparation method of the present invention adopts a two-step sintering method. In the first step, i.e., in the reaction stage of oxide film removal, a relatively low temperature is adopted and a high-flow high-purity nitrogen atmosphere is introduced; a nitridation reaction occurs on the surface oxide film, the removal of the oxide film is accelerated, and thus the sintering of aluminum powder particles is promoted. Meanwhile, the secondary oxidation of aluminum alloy powder can be suppressed, and a foundation is laid for the subsequent vacuum sintering. After the oxide film is removed, a liquid phase has been formed in the silicon carbide reinforced aluminum-based composite material. At this time, the second step of sintering is carried out, and a high vacuum sintering mode is adopted. The liquid phase formed by increasing the temperature has good wettability with silicon carbide and aluminum alloy matrix at high temperature, and liquid phase sintering densification is achieved. The use of high vacuum can improve the wettability of the liquid phase, increase the capillary force during the sintering process, and allow the liquid phase to penetrate into the matrix, thereby improving the sintering density of the composite material.
[0008] Of course, the temperature in the first step cannot be too low. If it is too low, the aluminum oxide film layer cannot be eliminated, resulting in difficulty in forming the liquid phase in the second step or the aluminum alloy matrix being wrapped by the oxide film, inhibiting the sintering process. During the second step of sintering, if the temperature is too high or too low, the sintering process cannot be promoted, or overburning may occur.
[0009] In a preferred embodiment, the sintering aid powder is composed of Mg2Si powder, Al2Cu powder and Sn powder. The raw material powder has the following composition by mass percentage: 5~20wt% silicon carbide powder, 1~3wt% sum of Mg2Si powder and Al2Cu powder, 0.5~1.0wt% Sn powder, and the balance is aluminum alloy powder.
[0010] In the present invention, special sintering aids Mg2Si and Al2Cu are introduced, which have good wettability with silicon carbide and aluminum alloy powders in a high vacuum environment and can accelerate the densification process. In addition, the inventors found that Mg2Si powder can react with the oxide film to accelerate the removal process of the oxide film.
[0011] During the actual exploration process, the inventors also tried a large number of other sintering aids, but none of them could achieve the same effect as the sintering aids mentioned above in the present invention. For example, when adding aluminum-magnesium alloy and aluminum-silicon alloy powders, the inventors found that they could not break the oxide film, and Cu powder was also difficult to react with the oxide film on the aluminum surface at low temperatures.
[0012] Of course, the amount of Mg2Si powder and Al2Cu powder added in the present invention also needs to be effectively controlled. If it is too little, no effect will be achieved, and if it is too much, the performance of the material itself will be reduced.
[0013] Further preferably, the raw material powder has the following composition by mass percentage: 5-20wt% silicon carbide powder, 1-2wt% Mg2Si powder, 0.5-1wt% Al2Cu powder, 0.5-1.0wt% Sn powder, and the remainder is aluminum alloy powder.
[0014] In a preferred embodiment, the aluminum alloy powder is selected from any one of 2 series aluminum alloy, 6 series aluminum alloy and 7 series aluminum alloy.
[0015] In a preferred embodiment, the particle size of the silicon carbide powder is 0.2-5.0 μm, more preferably 0.5-3.0 μm. The inventors have found that the performance of the final material is optimal when the particle size of the silicon carbide powder is controlled within the above range. If the particle size is too small, the uniformity in the matrix will be reduced, and if the particle size is too large, it will affect the sintering densification.
[0016] In a preferred embodiment, the binder is selected from at least one of polyethylene glycol, paraffin wax and rubber, and the amount of the binder added is 1.0-2.0 wt % of the mixed powder mass.
[0017] In a preferred embodiment, the organic solvent is selected from at least one of anhydrous ethanol and hexane.
[0018] Preferably, the mixing method is ball milling.
[0019] In a preferred embodiment, the granulation method is spray granulation, and the spray granulation temperature is 60-100° C. In spray granulation, since the atomized slurry is in the form of very fine droplets, the specific surface area is large, so that the water in the droplets evaporates quickly, and the drying is completed quickly to obtain granulated powder.
[0020] In a preferred embodiment, the average particle size (D50) of the composite powder is 50-100 μm.
[0021] Preferably, the compression molding pressure is 100-300 MPa.
[0022] In a preferred embodiment, the degreasing is carried out in a hydrogen atmosphere, the degreasing temperature is 400-450°C, the holding time is 1-3 hours, and the heating rate is 0.5-2°C / min. In the present invention, degreasing in a hydrogen atmosphere can remove the carbon remaining in the binder and accelerate the polymer removal speed, so that it reacts completely at a lower temperature.
[0023] In a preferred embodiment, during the first sintering step, the flow rate of nitrogen is (1.5-2.0)×V (L / min), where V is the effective volume of the furnace and the positive pressure of the furnace is 1000-2000 Pa. In the present invention, controlling the flow rate of nitrogen within the above range can have two benefits: 1) accelerating the removal of the oxide film on the surface of the aluminum alloy powder; 2) eliminating the oxygen atmosphere in the furnace, obtaining a low oxygen partial pressure, and preventing the secondary oxidation of the aluminum alloy powder. For example, if the furnace is 5L, the nitrogen flow rate is (7.5-10) L / min.
[0024] Principles and advantages The preparation method of the present invention is, first, to adopt a two-step sintering method. The first step is to introduce a high-flow high-purity nitrogen atmosphere in the reaction stage of breaking the oxide film; so that the surface oxide film undergoes a nitridation reaction, accelerates the breaking of the oxide film, and thus promotes the sintering of aluminum powder particles. At the same time, the secondary oxidation of the aluminum alloy powder can be suppressed, paving the way for the subsequent vacuum sintering. After the oxide film is broken, the liquid phase has been formed in the silicon carbide reinforced aluminum-based composite material. At this time, the second step of sintering is carried out, and a high vacuum sintering mode is adopted to improve the wettability of the liquid phase, increase the capillary force during the sintering process, and allow the liquid phase to penetrate into the matrix to improve the sintering density of the composite material; second, two components of the added phase Mg2Si and Al2Cu are added, which can not only break the oxide film, but also have good wettability with silicon carbide and aluminum alloy powder, which can accelerate the sintering densification of the second stage. Through the synergy of various processes in the preparation method of the present invention, the relative density of the silicon carbide reinforced aluminum-based composite material can be obtained to be more than 98.5%, and at the same time, the silicon carbide particles are evenly distributed, and the comprehensive mechanical properties of the composite material are excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 , the morphology and structure of the silicon carbide reinforced aluminum-based composite material obtained by two-step sintering in Example 1.
[0026] Figure 2 , the morphology and structure of the silicon carbide reinforced aluminum-based composite material prepared by two-step sintering in Comparative Example 1. DETAILED DESCRIPTION
[0027] Example 1
[0028] (1) First, silicon carbide powder, sintering aid powder and aluminum alloy powder are mixed, and a small amount of binder and organic solvent are added, and then ball milling is performed. After ball milling is completed, spray granulation is performed. Since the atomized slurry is in the form of very fine droplets, the specific surface area is large, so the water in the droplets evaporates quickly and the drying is completed quickly to obtain granulated powder. Then sieve to obtain a composite spherical powder.
[0029] The components of the silicon carbide reinforced aluminum-based composite material are as follows: the mass fraction of silicon carbide powder is 10wt%; the sintering aid powder is composed of 1wt% Mg2Si and 1wt% Al2Cu, and also contains 0.5wt% Sn powder; the remainder is aluminum alloy powder, which can be 7075 series aluminum alloy.
[0030] The particle size of the silicon carbide powder is 2.0 microns.
[0031] The binder is selected from polyethylene glycol, the binder accounts for 1.0wt% of the mass fraction of the composite powder, and the solvent is anhydrous ethanol.
[0032] Preferably, the spray drying temperature is 70° C., and the average particle size (D50) of the composite powder is preferably 50 μm.
[0033] (2) Subsequently, the silicon carbide reinforced aluminum-based composite powder is subjected to compression molding at a molding pressure of 100 MPa, and then a composite material blank is obtained.
[0034] (3) Subsequently, the formed body was degreased in a hydrogen atmosphere at a degreasing temperature of 420°C, a holding time of 2 h, and a heating rate of 0.5°C / min.
[0035] (4) The two-step sintering preparation method of a silicon carbide reinforced aluminum-based composite material described in this case comprises the following steps: the degreased composite body is subjected to two-step sintering, the first step being sintering in a high nitrogen flow atmosphere, wherein the sintering temperature is 530°C and the holding time is 60 min; then, the furnace is evacuated and the nitrogen supply is stopped, the vacuum sintering temperature is 610°C and the holding time is 90 min, after which the silicon carbide particle reinforced aluminum-based composite material can be obtained.
[0036] In the first step, the nitrogen flow rate of high nitrogen flow atmosphere sintering is 3.0 (L / min), where the effective volume of the furnace is 2L.
[0037] The vacuum degree of vacuum sintering in the second step needs to avoid oxidation of the alloy powder, and the vacuum degree is 1.0×10 -4 Pa.
[0038] The silicon carbide reinforced aluminum-based composite material prepared by this technical method can obtain a relative density of 98.7% for the composite material, a yield strength of 420 MPa, a tensile strength of 380 MPa, an elastic modulus of 110 GPa, and an elongation of 7.4%.
[0039] Example 2
[0040] (1) First, silicon carbide powder, sintering aid powder and aluminum alloy powder are mixed, and a small amount of binder and organic solvent are added, and then ball milling is performed. After ball milling is completed, spray granulation is performed. Since the atomized slurry is in the form of very fine droplets, the specific surface area is large, so the water in the droplets evaporates quickly and the drying is completed quickly to obtain granulated powder. Then sieve to obtain a composite spherical powder.
[0041] The components of the silicon carbide reinforced aluminum-based composite material are as follows: the mass fraction of silicon carbide powder is 15wt%; the sintering aid powder is composed of 2wt% Mg2Si and 0.5wt% Al2Cu, and also contains 0.8wt% Sn powder; the remainder is aluminum alloy powder, which can be 6061 series aluminum alloy.
[0042] The particle size of the silicon carbide powder is 5.0 microns.
[0043] The binder is selected from paraffin, the binder accounts for 2.0wt% of the mass fraction of the composite powder, and the solvent is n-hexane.
[0044] The spray drying temperature is 60° C., and the average particle size (D50) of the composite powder is preferably 100 μm.
[0045] (2) Subsequently, the silicon carbide reinforced aluminum-based composite powder is subjected to compression molding at a molding pressure of 200 MPa, and then a composite material blank is obtained.
[0046] (3) Subsequently, the formed body was degreased in a hydrogen atmosphere at a degreasing temperature of 400°C, a holding time of 2 h, and a heating rate of 1°C / min.
[0047] (4) The two-step sintering preparation method of a silicon carbide reinforced aluminum-based composite material described in this case comprises the following steps: the degreased composite body is subjected to two-step sintering, the first step being sintering in a high nitrogen flow atmosphere, wherein the sintering temperature is 520°C and the holding time is 60 min; then, the furnace is evacuated and the nitrogen supply is stopped, the vacuum sintering temperature is 630°C and the holding time is 60 min, after which the silicon carbide particle reinforced aluminum-based composite material can be obtained.
[0048] In the first step, the nitrogen flow rate of high nitrogen flow atmosphere sintering is 4.0 (L / min), where the effective volume of the furnace is 2L.
[0049] The vacuum degree of vacuum sintering in the second step needs to avoid oxidation of the alloy powder, and the vacuum degree is 3.0×10 -4 Pa.
[0050] The silicon carbide reinforced aluminum-based composite material prepared by this technical method can obtain a relative density of 98.9% for the composite material. The composite material has a yield strength of 450 MPa, a tensile strength of 410 MPa, an elastic modulus of 130 GPa, and an elongation of 6.5%.
[0051] Example 3
[0052] (1) First, silicon carbide powder, sintering aid powder and aluminum alloy powder are mixed, and a small amount of binder and organic solvent are added, and then ball milling is performed. After ball milling is completed, spray granulation is performed. Since the atomized slurry is in the form of very fine droplets, the specific surface area is large, so the water in the droplets evaporates quickly and the drying is completed quickly to obtain granulated powder. Then sieve to obtain a composite spherical powder.
[0053] The components of the silicon carbide reinforced aluminum-based composite material are as follows: the mass fraction of silicon carbide powder is 20wt%; the sintering aid powder is composed of 2wt% Mg2Si and 1wt% Al2Cu, and also contains 1.0wt% Sn powder; the remainder is aluminum alloy powder, which can be 7075 series aluminum alloy.
[0054] The particle size of the silicon carbide powder is 3.0 microns.
[0055] The binder is selected from polyethylene glycol, the binder accounts for 1.5wt% of the mass fraction of the composite powder, and the solvent is anhydrous ethanol.
[0056] The spray drying temperature is 80° C., and the average particle size (D50) of the composite powder is preferably 80 μm.
[0057] (2) Subsequently, the silicon carbide reinforced aluminum-based composite powder is subjected to compression molding at a molding pressure of 150 MPa, and then a composite material blank is obtained.
[0058] (3) Subsequently, the formed body was degreased in a hydrogen atmosphere at a degreasing temperature of 450°C, a holding time of 2 h, and a heating rate of 0.5°C / min.
[0059] (4) The two-step sintering preparation method of a silicon carbide reinforced aluminum-based composite material described in this case comprises the following steps: the degreased composite body is subjected to two-step sintering, the first step being sintering in a high nitrogen flow atmosphere, wherein the sintering temperature is 520°C and the holding time is 120 min; then, the furnace is evacuated and the nitrogen supply is stopped, the vacuum sintering temperature is 640°C and the holding time is 60 min, after which the silicon carbide particle reinforced aluminum-based composite material can be obtained.
[0060] In the first step, the nitrogen flow rate of high nitrogen flow atmosphere sintering is 3.0 (L / min), where the effective volume of the furnace is 2L.
[0061] The vacuum degree of vacuum sintering in the second step needs to avoid oxidation of the alloy powder, and the vacuum degree is 1.0×10 -4 Pa.
[0062] The silicon carbide reinforced aluminum-based composite material prepared by this technical method can obtain a relative density of the composite material of 98.5%. The composite material has a yield strength of 430 MPa, a tensile strength of 390 MPa, an elastic modulus of 150 GPa, and an elongation of 5.4%.
[0063] Comparative Example 1 The preparation method of this comparative example is basically the same as that of Example 1, except that in this comparative example, silicon carbide powder and sintering aid powder are selected, wherein the sintering aid only contains Sn, and no Mg2Si and Al2Cu. Other process conditions and parameters are the same as those of Example 1. The relative density of the composite material can be obtained to be 97.2%, and the yield strength of the composite material is 320 MPa, the tensile strength is 270 MPa, the elastic modulus is 100 GPa, and the elongation is 4.6%.
[0064] Comparative Example 2 The preparation method of this comparative example is basically the same as that of Example 1, except that this comparative example uses only nitrogen atmosphere for sintering during the sintering process, and nitrogen flow is still introduced during the subsequent vacuum sintering process without vacuuming. Other process conditions and parameters are the same as those of Example 1. The relative density of the composite material can be obtained to be 97.5%, and the yield strength of the composite material is 360 MPa, the tensile strength is 320 MPa, the elastic modulus is 105 GPa, and the elongation is 5.2%.
[0065] Comparative Example 3 The preparation method of this comparative example is basically the same as that of Example 1, except that the nitrogen flow rate of the nitrogen atmosphere sintering during the sintering process of this comparative example is only 1.0 L / min. Other process conditions and parameters are the same as those of Example 1. The relative density of the composite material can be obtained to be 98.0%, and the yield strength of the composite material is 350 MPa, the tensile strength is 330 MPa, the elastic modulus is 110 GPa, and the elongation is 5.5%.
[0066]
Claims
1. A method for preparing a silicon carbide reinforced aluminum-based composite material, characterized in that: The raw material powder, the binder and the organic solvent are mixed to obtain a mixed powder, wherein the raw material powder consists of silicon carbide powder, sintering aid powder and aluminum alloy powder; the mixed powder is sequentially granulated and sieved to obtain a composite powder, the composite powder is molded to obtain a composite material blank, the composite material blank is degreased to obtain a degreased blank, the degreased blank is sintered in two steps, the first step is sintered in a nitrogen atmosphere, the first step is sintered at a temperature of 520-550°C, the first step is sintered for 30-60 minutes, the second step is sintered in a vacuum environment, the second step is sintered at a temperature of 600-640°C, the second step is sintered for 60-90 minutes, and a silicon carbide reinforced aluminum-based composite material is obtained after the two-step sintering is completed.
2. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1, characterized in that: The sintering aid powder is composed of Mg2Si powder, Al2Cu powder and Sn powder. The raw material powder has the following composition by mass percentage: 5-20wt% silicon carbide powder, 1-3wt% of the sum of Mg2Si powder and Al2Cu powder, 0.5-1.0wt% Sn powder, and the balance is aluminum alloy powder.
3. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The raw material powder has the following composition by mass percentage: 5-20wt% silicon carbide powder, 1-2wt% Mg2Si powder, 0.5-1wt% Al2Cu powder, 0.5-1.0wt% Sn powder, and the balance is aluminum alloy powder.
4. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The aluminum alloy powder is selected from any one of 2 series aluminum alloy, 6 series aluminum alloy and 7 series aluminum alloy; The particle size of the silicon carbide powder is 0.2-5.0 μm. The binder is selected from at least one of polyethylene glycol, paraffin wax and rubber, and the amount of the binder added is 1.0-2.0wt% of the mixed powder mass; The organic solvent is selected from at least one of anhydrous ethanol and hexane.
5. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The mixing method is ball milling.
6. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The granulation method is spray granulation, and the temperature of the spray granulation is 60-100°C.
7. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The average particle size of the composite powder is 50-100 μm.
8. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The compression molding pressure is 100-300 MPa.
9. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: The degreasing is carried out in a hydrogen atmosphere, the degreasing temperature is 400-450° C., the heat preservation time is 1-3 hours, and the heating rate is 0.5-2° C. / min.
10. The method for preparing a silicon carbide reinforced aluminum-based composite material according to claim 1 or 2, characterized in that: During the first step of sintering, the flow rate of nitrogen is (1.5~2.0)×V (L / min), where V is the effective volume of the furnace and the positive pressure of the furnace is 1000~2000Pa.
Citation Information
Patent Citations
Pressureless sintering-pressurized densifying preparation method for titanium-aluminum-carbon particle enhanced zinc-aluminum matrix composite
CN104099488A
Aluminum alloy injection molding method
CN115582545A
Aluminum alloy composite material and injection molding preparation method thereof
CN116100023A
Preparation method of silicon carbide particle reinforced aluminum-based composite material with medium and high volume fractions
CN116752028A
Method for Preparing Aluminum Nitride Powder bySelf-propagating High-temperature Synthesis
KR1020020023570A